Las Variaciones lingüísticas en el dialecto iraquí y sus equivalentes en el idioma español: Frankenstein en Bagdad un modelo ejemplar - Ahmed, Wisam; Qays, Gheidaa (Al-Adab Journal, 2022)
The reason for presenting this work can be summarized in the following points: To draw attention to the linguistic variations that make the Arabic language a richly expressive language. To exhibit a sufficient amount of the differences in linguistic value and the differences in expressing a sentence in the Iraqi Arabic dialect of a literary work, written in the same dialect, under the name Frankenstein in Baghdad (FB), translated into the language Spanish. To focus the light on translation errors. We will explain the reasons for this type of error and how to analyze it in the following pages. It is a common mistake that translators make, particularly when relating to an Arabic proverb or a saying of ethnic or religious origin. The opposite for parts of the classical Arabic language. Since the exact and natural meaning is found when transferring a value from standard Arabic to Castilian Spanish. It is known how to equate the term (in God we trust بمشيئة الله او توكلنا على الله) to Spanish because it is a shared factor, rather a common linguistic aspect. To know why errors occur in transferring information in places where Spanish is a pure language and Arabic is a language of multiple diversities, due to historical changes in meaning. That is why it happens that care is not taken in translating the cultural part and the origin of a locution is not sought. This type of analysis would be very beneficial to us and enables us to avoid any futuristic error by following the steps of the contrastive analysis of cultural aspects. We personally believe that the difference in the way the Arabic language is formed from that of Spanish and the transfer of meaning between using the slang of the Iraqi dialect would be more similar if we had found an equivalent in the Spanish slang.